Which expression represents the volume of the box? use the formula v=lwh 3x+1, 2x-1 ×+2

Skip to content# Which expression represents the volume of the box? use the formula v=lwh 3x+1, 2x-1 ×+2

Mathematics ##
Comments (5) on “Which expression represents the volume of the box? use the formula v=lwh 3x+1, 2x-1 ×+2”

### Leave a Reply Cancel reply

Which expression represents the volume of the box? use the formula v=lwh 3x+1, 2x-1 ×+2

The expression of the volume of the box with dimensions of

(3x+1) by (2x-1) by (x+2) will be:

volume, V=lwh

plugging the values we get:

V=(3x+1)(2x-1)(x+2)

Expanding the above we get:

V=(3x+1)(2x^2+3x-2)

V=3x(2x^2+3x-2)+1(2x^2+3x-2)

V=6x^3+9x^2-6x+2x^2+3x-2

V=6x^3+11x^2-3x-2

Hence the expression for the volume will be:

V=6x^3+11x^2-3x-2

1. The formula for calculate the volume of the box is shown in the problem:

V=lwh

V is the volumen of the box.

l is the length of the box.

w is the widht of the box.

2. When you substitute the values shown in the figure attached, into the formula V=lwh, you obtain:

V=(2x-1)(x+2)(3x+1)

3. You must apply the "Distributive property". Then, you have:

V=6x³+11x²-3x-2

Which expression represents the volume of the box?

The second expression, which is: 6x³+11x²-3x-2

The volume is the product of the 3 dimensions

= (x + 2)(2x - 1)(3x + 1)

= (x + 2)(6x^2 -x - 1)

= 6x^3 - x^2 - x + 12x^2 -2x - 2

= 6x^3 + 11x^2 - 3x - 2 Answer

Its choice 3.

D. 6x³ + 5x² - 3x - 2

Step-by-step explanation:

First assign each variable with its number.

l = 2x + 1

w = x + 1

h = 3x - 2

Now, plug in.

v = (2x + 1)(x +1)(3x - 2)

Now combine the first two pairs following the FOIL method. (First Outer Inner Last)

(2x² + 3x + 1)(3x - 2)

Now you would multiply the 3x on to each term and the -2 on to each term.

6x³ + 9x² + 3x - 4x² - 6x - 2

Now combine like terms.

6x³ + 5x² - 3x - 2

3. 6x^3 + 11x^2 - 3x - 2